2012
DOI: 10.1177/1090198112465088
|View full text |Cite
|
Sign up to set email alerts
|

Empowered Diabetes Management

Abstract: The Hawai'i Demonstration to Maintain Independence and Employment was a randomized controlled trial examining the effect of a participant-driven, multicomponent intervention on 190 employed adults with diabetes, 36% of whom were Asian and 35% of whom were Native Hawaiian or Pacific Islander. A no treatment concurrent control group was used, and the treatment group was provided an intervention that paired each participant with a life coach and a pharmacist counselor with whom they worked to achieve collaborativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The duration of the interventions ranged from 4 weeks to 18 months. Studies showed improvements in self-efficacy and knowledge of self-management [[32], [33], [34], [35], [36]]. Results for reduction in HbA1c were mixed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the interventions ranged from 4 weeks to 18 months. Studies showed improvements in self-efficacy and knowledge of self-management [[32], [33], [34], [35], [36]]. Results for reduction in HbA1c were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Results for reduction in HbA1c were mixed. Four studies described reductions in HbA1c levels in peer-led intervention groups and CHWs [1,28,31,37]; three studies showed no significant reduction in HbA1c levels [32,33,38].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several studies incorporating QOL on seven attributes, namely, vision, hearing, speech, ambulation, dexterity, emotion, and cognition, reported positive results [ 76 , 80 , 92 ]. QOL measurement is widely accepted as an important goal in health interventions [ 32 ] and these studies provide evidence for pharmacists' value in improving both clinical and QOL outcomes for diabetes patients.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, this improvement did not correlate with the number of sessions in which the patient participated [23]. In another intervention, empowerment support through a life coach and pharmacist counselor led to positive effects in terms of self-efficacy, quality of life, and body mass index (BMI), but no improvement in metabolic control (measured by glycated hemoglobin [HbA1c] levels) was observed [24]. Previous studies have confirmed the positive effect of empowerment and education on metabolic control and quality of life of patients with diabetes.…”
Section: The Effects Of Empowerment Therapy In Type 2 Diabetes Andmentioning
confidence: 99%